Analisis Kegiatan Ekstrakurikuler Dalam Pengembangan Potensi Peserta Didik Di MTS Negari 4 Mandailing Natal - Kasman Kasman; Nur Paridah; Juli Annisa Nasution; Apsah Apsah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
In the realm of education, which prioritizes the holistic development of students' potential, extracurricular activities play an indispensable role. They not only complement the academic curriculum but also serve as effective avenues for shaping character, honing skills, and unearthing students' talents beyond the classroom. Through in-depth analysis of extracurricular activities, we can gain a better understanding of their contributions to students' potential development. This research aims to provide insights into how extracurricular activities play a crucial role in shaping the character, skills, and talents of students at MTs Negeri 4 Mandailing Natal.This study employs a qualitative approach with a focus on phenomenology. The research location is at MTs Negari 4 Mandailing Natal, located in Sumatra Utara. Data were obtained through interviews with the school principal, teachers, and members of the change agents. The implementation of extracurricular activities in developing students' interests and talents requires careful planning. Discussions on the analysis of extracurricular activities at MTs Negari 4 Mandailing Natal encompass various aspects, ranging from the types of activities, student participation, influence on character formation, to skills and talent development.Extracurricular activity supervisors play a vital role in planning activities and ensuring their implementation aligns with the intended goals. The success of extracurricular activities heavily relies on collaboration among the school principal, activity supervisors, and students. With extracurricular activities in place, MTs Negari 4 Mandailing Natal has witnessed significant developments in students' interests and talents, providing positive impacts not only for the students themselves but also for the educational institution and the surrounding community. Keywords: , , ,